Improving Social Skills Using the Group Experiment Method in Class A Children of Kartika IV-17 Kindergarten, Madiun City - Nurul Liyana; Muhammad Hanif; Parji Parji (Jurnal Paradigma, 2026)
Abstract This study aims to improve the social skills of Class A students at TK Kartika IV-17 Kota Madiun, who generally still demonstrate low levels of social competence, particularly in the areas of cooperation, communication, sharing, participation, and adaptation. One contributing factor to this low level of social skill is that previous learning activities did not provide sufficient direct and collaborative experiences that enable children to interact optimally. Therefore, this research was conducted to enhance children’s social skills through the implementation of the group experiment method. The study employed a Classroom Action Research (CAR) design consisting of two cycles, each involving planning, implementation of actions, observation, and reflection. Data were collected through observation and documentation and were analyzed qualitatively to identify improvements in children’s social development. The findings indicate that the group experiment method effectively improved children’s social skills. The total social skill score increased from 134 in the pre-cycle phase (Beginning to Develop) to 190 in Cycle I (Beginning to Develop) and rose significantly to 350 in Cycle II (Developing Very Well). Classically, all 19 children reached the BSH and BSB categories in Cycle II, surpassing the performance indicator of 80%. Thus, the group experiment method proved effective in providing active, collaborative, and meaningful learning experiences that enhance the social skills of Class A students at TK Kartika IV-17 Madiun City.